Selenium enhances ROS scavenging systems and sugar metabolism increasing growth of sugarcane plants - Araujo, Maycon Anderson de [UNESP]; Melo, Andressa Aparecida Rodrigues de [UNESP]; Silva, Vinicius Martins [UNESP]; Reis, André Rodrigues dos [UNESP] (Elsevier, 2023)
Selenium (Se) beneficial effect on plants is related to an increase in nitrogen (N) assimilation and its role as an abiotic stress mitigator by reactive oxygen species (ROS) scavenging enhanced by antioxidant metabolism. This study aimed to evaluate sugarcane (Saccharum spp.) growth, photosynthetic and antioxidant responses, and sugar accumulation in response to Se supply. The experimental design was a factorial scheme 2 × 4: two sugarcane varieties (RB96 6928 and RB86 7515) and four Se application rates (0; 5; 10 and 20 μmol L−1) applied as sodium selenate in the nutrient solution. Leaf Se concentration increased under Se application in both varieties. The enzymes SOD (EC 1.15.1.1) and APX (EC 1.11.1.11) showed increase activities under Se application on variety RB96 6928. Nitrate reductase activity increased in both varieties resulting in the conversion of nitrate into higher total amino acids concentration indicating an enhanced N assimilation. This led to an increased concentration of chlorophylls and carotenoids, increased CO2 assimilation rate, stomatal conductance, and internal CO2 concentration. Selenium provided higher starch accumulation and sugar profiles in leaves boosting plant growth. This study shows valuable information regarding the role of Se on growth, photosynthetic process, and sugar accumulation in sugarcane leaves, which could be used for further field experiments. The application rate of 10 μmol Se L−1 was the most adequate for both varieties studied considering the sugar concentration and plant growth.
Keywords: Antioxidant system; Nitrogen metabolism; Saccharum spp; Sodium selenate; Sugar metabolism